Epileptic seizure after treatment with thiocolchicoside - Pedro Giavina-Bianchi; Mara Giavina-Bianchi; Luciana Kase Tanno; et al (Dove Medical Press, 2009)
Pedro Giavina-Bianchi1,2, Mara Giavina-Bianchi1, Luciana Kase Tanno1, Luis Felipe Chiaverini Ensina1, Antôno Abílio Motta1, Jorge Kalil1,21Division of Clinical Immunology and Allergy, University of São Paulo, São Paulo, SP, Brazil; 2Institute of Science, Hospital Alemao Oswaldo CruzBackground: Adverse drug reactions are important determinants of inpatient and outpatient morbidity. Thiocolchicoside is a semisynthetic derivate of naturally occurring colchicoside, which is largely used in humans as a centrally acting muscle relaxant. Epileptic seizures after thiocolchicoside intake have been reported in individuals with a history of epilepsy, acute brain injury or possible blood–brain barrier disruption.Case report: We report the case of a 66-year-old male patient presenting a sudden epileptic seizure temporally related to the intake of thiocolchicoside for muscle contracture and pain. The probably causes of the seizures were thiocolchicoside intake and cerebral microhemorrhages attributed to cerebral amyloid angiopathy.Discussion: Drugs only rarely cause focal seizures. Our case indicates that thiocolchicoside can precipitate seizures in predisposed patients, and that its use should be avoided in patients with brain diseases (and therefore lower seizure thresholds) or blood–brain barrier disruption. This information should be provided in the drug package insert.Keywords: adverse drug reaction, thiocolchicoside, coltrax, epileptic seizure, muscle relaxant, cerebral amyloid angiopathy